Lachester’s equations as a simple strategic decision tools - Kostić, Mladen; Jovanovic , Aca (Serbian Journal of Management, 2023)
This paper have researched Lachester’s equations method as a simple simulation modeling of heterogenic force combat in operations regarding optimal operational concept method as a secondary analytical tool. According to this hypothesis it was created six courses of engagement heterogenic combat forces. Mathematical model developed by Lachester’s equations, quadratic and linear law, for use in combat of two opponents with heterogenic force structure (air force and army). Created simplified model is helpful and enables righteous analysis for decision making process. That witnesses practical use of this method as a secondary analytical tool. Real war and combat operations are very complex and for that reason decision makers need applications of some approximated methods in simulation and modeling like Lachester’s equations.